Trump's Trade Policy Agenda - Christoph Scherrer; Elizabeth Abernathy (Intereconomics, 2017)
President Donald Trump espouses “America First” positions which are commonly interpreted as protectionist. However, a closer reading of Donald Trump's business interests, of his administration's published trade agenda and of US trade negotiation history calls into question whether “America First” means protectionism. Trump will use large trade deficits to pressure trading partners to further open up their markets. Companies that are successful in exporting to the US market from those countries will be alarmed by protectionist announcements and will therefore most likely pressure their governments to give in to the demands of the Trump administration.
Keywords: 330